Robot-assisted laparoscopic ipsilateral ureteroureterostomy for duplex kidneys in children: preliminary single-center experience - Yang, Chao; Zhang, Chi; Cao, Yongsheng; Deng, Qi-fei; Mao, Changkun (Frontiers in Pediatrics, 2025)
ObjectiveThis study evaluates the efficacy and safety of robot-assisted laparoscopic ipsilateral ureteroureterostomy (RAL-IUU) in treating children with duplex kidney ureteral malformations by detailing our early single-center experience.Materials and methodsWe conducted a retrospective analysis of clinical data from 14 children with complete duplex kidney ureteral malformations treated with RAL-IUU at our institution from December 2021 to January 2024. Clinical data included patient demographics, surgical details, and postoperative outcomes.ResultsThe operation time averaged 128.71 ± 22.35 min in 14 cases, intraoperative blood loss was 7.57 ± 2.77 ml, drainage tube placement lasted for 3.14 ± 0.66 days, and hospital stay averaged 4.79 ± 0.70 days. Stent placement lasted 43.58 ± 6.33 days. Notable changes were observed in the upper moiety anterior-posterior diameter (APD) before and after surgery (23.84 ± 8.05 mm vs. 6.71 ± 2.20 mm, P < 0.001), diameter at the widest part of the upper moiety ureter (15.58 ± 6.07 mm vs. 4.61 ± 0.78 mm, P < 0.001), and split renal function of the upper moiety (12.28 ± 3.04% vs. 16.50 ± 2.75%, P < 0.001). Postoperative follow-up ranged from 6 to 18 months; during the period with a D-J stent, one case developed a urinary tract infection, one case had recurrent gross hematuria, and another child exhibited significant urinary irritative symptoms (frequency), with an abdominal plain film revealing that the D-J tube had descended completely into the bladder, and symptoms disappeared after the removal of the D-J tube. During the follow-up period post-D-J tube removal, none of the 14 children experienced a urinary tract infection again during the follow up period, urinary incontinence ceased.ConclusionRAL-IUU provides an excellent surgical field and operating space, precise suturing, and minimal surgical trauma. Postoperatively, there is a reduction in renal pelvis and ureteral hydronephrosis, recovery of split renal function, and minimal complications all with rapid recovery. RAL-IUU is a safe and feasible treatment option for children with complete duplex kidneys.